Perkembangan kognitif dalam Islam dan model bioekologi urie bronfenbrenner untuk hidup di era revolusi 4.0 - Perdana, Riki (Universitas Negeri Yogyakarta, 2019)
Human development is influenced by many factors so that each stage requires different treatments in order to become fully human. This study aims to describe the human development of the bioecological model and be related to the concept of human development in Islam. The method used is a literature review, by reviewing a number of scientific articles published from 2010 - 2020. Articles obtained from a number of indexed journals such as Google Scholar, Copernicus, Scopus Elsevier, Sage publication and other indexes. The results showed that there were five (5) stages of human development in the bioecological model including microsystems, mesosystems, ecosystems, macrosystems, and chronosystems. There are nine (9) stages of human development in an Islamic perspective ranging from 0 years to 80 years and above. In life in the era of industrial revolution 4.0 there are several points that become basic principles such as flexibility, efficiency, digitalization, decentralization, and individualization of needs. The conclusion of this research is that for every child development, it cannot be carried out directly with the pattern of the industrial revolution 4.0, each stage requires a different treatment so that the pattern of life in accordance with the Islamic religious guidance without lagging with the current of globalization. Perkembangan manusia dipengaruhi oleh banyak faktor sehingga setiap tahap membutuhkan perlakuan yang berbeda agar dapat menjadi manusia seutuhnya. Penelitian ini bertujuan untuk mendeskripsikan perkembangan manusia model bioekologi dan dihubungkan dengan konsep perkembangan manusia dalam islam. Metode yang dilakukan adalah literature review, dengan merivew sejumlah artikel ilmiah yang terbit sejak tahun 2010 – 2020. Artikel diperoleh dari sejumlah jurnal terindeks seperti google scholar, copernius, scopus Elsevier, Sage publication dan indeks lain. Hasil penelitian menunjukkan bahwa ada lima (5) meliputi mikrosistem, mesosistem, eksosistem, makrosistem dan kronosistem. Terdapat Sembilan (9) tahapan perkembangan manusia mulai dari 0 th hingga 80 th ke atas. Dalam kehidupan di era revolusi industri 4.0 ada beberapa poin yang menjadi prinsip dasar yaitu fleksibilitas, efisiensi, digitalisasi, desentralisasi dan individualisasi kebutuhan. Kesimpulan dari penelitian ini adalah pada setiap perkembangan anak, tidak bisa langsung dijalankan dengan pola revolusi industri 4.0, setiap tahapan memerlukan perlakukan yang berbeda agar pola kehidupan sesuai dengan tuntuan agama Islam tanpa tertinggal dengan arus globalisasi.